Cardiac surgeryEmergency reoperation after open heart surgery: ten years of experience - Yüksel, Volkan; Huseyin, Serhat; Canbaz, Suat; Ege, Turan; Sunar, Hasan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Postoperative bleeding is an important complication after open heart surgery. Resternotomy for bleeding is an important source of mortality and morbidity. Aim of the study: We aimed to identify the common sites of bleeding after open heart surgery and to present our results. Material and methods: We performed 2286 open heart operations from January 2003 to January 2013. Reoperation for bleeding was performed in the case of bleeding that exceeded 3 ml/kg/h in the first 3 hours, continued bleeding of more than 200 ml/h that did not cease, and in the event of clinical signs of tamponade. All patients were reoperated in the operating theatre. Patient data and bleeding sites were recorded. Results : 98 patients (4.3%) underwent reoperation for bleeding or tamponade. Non-surgical causes of bleeding were found in 44 patients (44.9%). The major sites of bleeding were the left side branch of the internal thoracic artery (17.4%) and the side branch of the saphenous vein graft (13.3%). Mortality occurred in 13 patients (13.3%). Conclusions: Emergency reoperation for bleeding or tamponade after open heart surgery is an important problem. A high percentage of reoperated cases were due to technical errors during graft harvesting. We cannot always avoid the hematologic factors causing bleeding, but we can reduce the number of correctable causes that are usually surgeon-related. This should also contribute to reducing mortality and morbidity after open heart surgery.